2010
DOI: 10.3109/13880200903190977
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of essential oils and methanol extracts of sweet basilOcimum basilicumoccurring in Bangladesh

Abstract: The antibacterial potential of essential oils and methanol extracts of sweet basil Ocimum basilicum L. (Lamiaceae) was evaluated for controlling the growth range of food-borne pathogenic bacteria. Essential oils extracted by hydrodistillation from the leaves and stems were analyzed by GC-MS. Fifty-seven compounds representing 94.9 and 96.1% of the total leaf and stem oils, respectively, were identified, of which methyl chavicol (36.7 and 29.9%), gitoxigenin (9.3 and 10.2%), trimethoquinol (10.3 and 8.4%), beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 28 publications
7
44
0
2
Order By: Relevance
“…In addition, it was evident that among the employed bacteria, Gram negative bacterial strains showed the highest sensitivity to all crude extracts at all concentrations. Our results are fully in line with earlier results presented 20, 21, 22. Rosmarinic acid has previously been shown to possess significant antimicrobial activity against different strains of Gram (+ and −) bacterial 11, 12…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, it was evident that among the employed bacteria, Gram negative bacterial strains showed the highest sensitivity to all crude extracts at all concentrations. Our results are fully in line with earlier results presented 20, 21, 22. Rosmarinic acid has previously been shown to possess significant antimicrobial activity against different strains of Gram (+ and −) bacterial 11, 12…”
Section: Discussionsupporting
confidence: 94%
“…However, methanol, water, butanol and ethyl acetate crude extracts did not show any activity against P. aeruginosa, S. aureus and P. vulgaris at any concentration. This might reflect the diversity of secondary metabolites and the compromise of their bioactivity by the polarity of extraction solvents 20, 21, 22. In addition, it was evident that among the employed bacteria, Gram negative bacterial strains showed the highest sensitivity to all crude extracts at all concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing ineffectiveness in the antibiotic activities used for controlling plant and animal pathogen [2][3][4] has become a big challenge among researchers, clinicians and policymakers. Antimicrobial synthetic products used in food industries are even not safer as for the human health is concerned, leading to chemical toxicity [5]. Although the new science of molecular-microbial interaction helps in understanding and resolving the antibiotic-resistant complex mechanism, but the more success lies in discovery of new medicines to control infections in this twenty-first century resistance era [1] and also to provide valuable information on medicinal plant, their parts used and methods of preparation for treating various diseases [6].…”
Section: Multiple Drug Resistance (Mdr) and Synthetic Food-a Great Comentioning
confidence: 99%
“…Although the new science of molecular-microbial interaction helps in understanding and resolving the antibiotic-resistant complex mechanism, but the more success lies in discovery of new medicines to control infections in this twenty-first century resistance era [1] and also to provide valuable information on medicinal plant, their parts used and methods of preparation for treating various diseases [6]. Altogether these and many more allied issues have drawn curiosity in searching for a new drug formulation [7,8] that are safer as food preservative [5] and can control diseases and food contamination caused by microbial activities.…”
Section: Multiple Drug Resistance (Mdr) and Synthetic Food-a Great Comentioning
confidence: 99%
“…The bactericidal actions of substituted phenols and the normal alkyl derivatives of p-chlorophenols were examined against Gram-negative and Gram-positive bacteria [10,11]. The antibacterial potential of essential oils of sweet basil Ocimum basilicum L. (Lamiaceae) containing 1.8% 4-MP and methanol extracts was evaluated for controlling the growth range of food-borne pathogenic bacteria [12]. It was reported that BHT at high levels as well as at lower levels found in foods might have anti-cancer properties, possibly by damaging free radicals or by stimulating the production of enzymes that detoxify carcinogens.…”
Section: Introductionmentioning
confidence: 99%